Предмет: Алгебра,
автор: www766
Решите уравнения (33.8-33.9):
33.8.
1) (х+1)³ - 4х = 5+x²(х+3);
3) (х+1)³+(х-1)³-2х³=12
Ответы
Автор ответа:
86
Ответ:
ниже~
Объяснение:
1) (х+1)³ - 4х = 5+x²(х+3)
х³+3х²+3х+1-4х=5+х³+3х²
3х+1-4х=5
-х+1=5
-х=5-1
-х=4
х=-4
3) (х+1)³+(х-1)³-2х³=12
х³+3х²+3х+1+х³-3х²+3х-1-2х³=12
0+6х=12
6х=12
х=2
Вот как то так,пользуйся
amuhamedova515:
не знаю
Похожие вопросы
Предмет: Математика,
автор: Sasharemizova2
Предмет: Алгебра,
автор: muslimkhan208
Предмет: Русский язык,
автор: Alexparhomov
Предмет: Математика,
автор: g031
Предмет: Информатика,
автор: Svetloozero137